2016
DOI: 10.26858/est.v2i3.3218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inflation and Exchange Rate Rupiah Toward Poverty and Unemployment in Indonesia (Case Study: Small Industry in the Tourist Area of Lombok)

Abstract: The purpose of this research are: (1). Evaluate the impact of inflation and the weakening of the rupiah against US $ against unemployment, poverty. (2). Obtain some alternative ways to overcome inflation and weakening of rupiah exchange rate against US dollar in maintaining stability of welfare of SMEs in Lombok region. (3) To evaluate the marketing system used by MSMEs (4) To know the obstacles faced by MSMEs (5) To know the related sectors in supporting the success of UMKM. Method of research used descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Nevertheless, the estimation result showed that inflation variable has no effect on poverty reduction, regardless of the good curb inflation in the regions. This finding is in contrast with previous research that inflation can influence rural poverty (Son & Kakwani, 2009;Supriyadi & Kausar, 2017). Similarly, NTP also does not influence poverty reduction.…”
Section: Resultscontrasting
confidence: 99%
“…Nevertheless, the estimation result showed that inflation variable has no effect on poverty reduction, regardless of the good curb inflation in the regions. This finding is in contrast with previous research that inflation can influence rural poverty (Son & Kakwani, 2009;Supriyadi & Kausar, 2017). Similarly, NTP also does not influence poverty reduction.…”
Section: Resultscontrasting
confidence: 99%
“…Several empirical studies on MSMEs on poverty and other economic indicators, such as Dartanto & Nurkholis (2013), have shown that the provision of micro-credit has a significant effect on poverty. Supriyadi and Kausar (2016) also found that SMEs are contributing to the economy and development in Indonesia. Other study similar to this study, Tareq & Rahman (2020) has argued that rural micro-enterprises play a significant role in reducing poverty.…”
Section: Influence Of the Number Of Micro And Small Enterprises And Micro And Small Labor On Poverty Rates In Indonesiamentioning
confidence: 94%
“…Previous research shows a significant influence between inflation rates, exchange rates, economic growth, and average wages on poverty (Supriyadi, 2017). In this study, the economic variables used are economic growth, exchange rates, and inflation to see their effect on foreign tourist arrivals to Indonesia.…”
Section: Research Implicationmentioning
confidence: 99%